2008
DOI: 10.1007/s10545-008-0864-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcobalamin (TC) deficiency—Potential cause of bone marrow failure in childhood

Abstract: It is unusual for inborn errors of metabolism to be considered in the investigative work-up of pancytopenia. We report a family in which the proband presented with failure to thrive at 2 months of age and subsequent bone marrow failure. A previous sibling had died at 7 months of age with suspected leukaemia. Haematological findings in the proband were significant for pancytopenia, and bone marrow aspiration showed dysplastic changes in all cell lineages. Urinary organic acid analysis revealed elevated methylma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
4
18
0
Order By: Relevance
“…The majority of circulating Cbl is bound to haptocorrin and therefore not affected by TC deficiency. Thus, serum Cbl levels were, as previously reported (Hakami et al 1971;Prasad et al 2008), in the normal range, except for patient 5 who had low levels. Normal serum Cbl levels excluded nutritional Cbl deficiency, congenital intrinsic factor deficiency, or a disorder of intestinal Cbl receptors, and led to investigation of Cbl transport and intracellular metabolism.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The majority of circulating Cbl is bound to haptocorrin and therefore not affected by TC deficiency. Thus, serum Cbl levels were, as previously reported (Hakami et al 1971;Prasad et al 2008), in the normal range, except for patient 5 who had low levels. Normal serum Cbl levels excluded nutritional Cbl deficiency, congenital intrinsic factor deficiency, or a disorder of intestinal Cbl receptors, and led to investigation of Cbl transport and intracellular metabolism.…”
Section: Discussionsupporting
confidence: 84%
“…About 45 TC-deficient patients have been reported (Kaikov et al 1991;Rosenblatt and Fenton 2001). The gene coding for TC (TCN2) was identified in 1995 (Regec et al 1995), and ten pathogenic mutations have further been reported (Haberle et al 2009;Li et al 1994a;Li et al 1994b;Namour et al 2003;Prasad et al 2008;Qian et al 2002;Ratschmann et al 2009). We report herein on five TCdeficient patients who exhibited six unreported TCN2 mutations defining two important coding regions in exons 4 and 8, which code for TC-TC receptor and TC-Cbl interaction domains, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Both children are now doing well on oral Vitamin B 12 (Cyanocobalamin 10 mg and 5 mg once daily respectively). Propionylcarnitine concentrations were not elevated in the newborn screening cards from the proband and sister, however as indicated in Prasad et al 2008, the analyses were performed on specimens retrieved from storage after 7 years and 5 years, respectively. The mother has delivered another son who is clinically asymptomatic at age 5 months but had a positive newborn screen for propionic/methylmalonic acidemia with an elevated C3 at 6.59 μM (0.68-3.9) and C3/C200.33.…”
mentioning
confidence: 99%
“…In a recent article we described two siblings with TC deficiency (Prasad et al 2008). The older child was clinically symptomatic with pancytopenia and his sister was diagnosed at birth by mutation analysis.…”
mentioning
confidence: 99%
“…(Prasad et al 2008;Trakadis et al 2013), methylmalonic aciduria (MMA; OMIM #251100, MMAA mutation) (Trakadis et al 2013), and intrinsic factor deficiency (IFD; OMIM #261000, GIF mutation) (Tanner et al 2005). Gastric intrinsic factor (GIF) is a cofactor produced by the parietal cells of the stomach.…”
mentioning
confidence: 99%